1995
DOI: 10.1002/pts.2770080202
|View full text |Cite
|
Sign up to set email alerts
|

Performance of aluminium trays for sterilized products

Abstract: The performance o f a retortable semi-rigid aluminium container, o f square shape, net capacity 330ml and w i t h a heat sealable lid, produced in Germany by Alcan, was studied relative t o parameters o f filling, thermal processing and heat sealing. Tests were applied t o packages containing water (275 and 295g) and a solution of carboxymethyl cellulose (CMC) at 1.25% (295 and 306g). The thermal processing was applied under stationary and rotary (at 8, 10 and 12 r.p.m.) conditions. Heat sealing was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Various researchers have reported the reduction in process time with the increase in rotation (Hersom and Hulland 1980;Knap and Durance 1998). Ortiz et al (1995) reported the reduction of sterilization time by approximately 50% in agitated products compared to stationary retorted products. Ali et al (2006) reported the reduction of process time with the increase in rotation of retort for tuna in oil medium processed in retortable pouches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers have reported the reduction in process time with the increase in rotation (Hersom and Hulland 1980;Knap and Durance 1998). Ortiz et al (1995) reported the reduction of sterilization time by approximately 50% in agitated products compared to stationary retorted products. Ali et al (2006) reported the reduction of process time with the increase in rotation of retort for tuna in oil medium processed in retortable pouches.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have reported the reduction in process time with the increase in rotation (Hersom and Hulland 1980; Knap and Durance 1998). Ortiz et al. (1995) reported the reduction of sterilization time by approximately 50% in agitated products compared to stationary retorted products.…”
Section: Introductionmentioning
confidence: 99%
“…The current study was conducted with a medium-low viscosity product, 12 cm on the Bostwick. Another study stated that rotary motion during thermal processing was more effective than stationary processing for high viscosity products, reducing processing time by approximately 50% (Ortiz, Alves, de Oliveira, de Almeida Anjos, & Goncalves, 1995).…”
Section: Difference Between Motions (Average Slope Of Heating Curves)mentioning
confidence: 99%
“…Reduction in process time will have an advantageous effect on the sensory and nutritional qualities of thermally processed fish products. Rotary thermal processing was found to be more advantageous than stationary thermal processing, mainly for a high viscosity medium as it reduced sterilization time by approximately 50% (Ortiz et al, 1995). Rotation of the cage of the retort has a positive effect on the heat penetration in retort pouches during thermal processing.…”
Section: Introductionmentioning
confidence: 99%